RESILIENCE, ACCOMMODATION AND SOCIAL CAPITAL SALAFI ISLAMIC EDUCATION IN LOMBOK - Muharir Alwan (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This study aims to find the social capital owned by Salafi education, which causes it thrive in the midst of resistance and diversity of Islamic educational institutions in Lombok. This field research uses qualitative-descriptive analysis, with the analytical framework of Reivich's theory of resilience, Shattle's and Boerdeou's social capital theory. The data was collected through observation, interviews, documentation and netnography; namely searches on social media such as on YouTube, Facebook, and online TV. The data are presented deductively and then processed using the Milles and Haberman procedure. Data analysis was carried out in several stages such as; data collection, data reduction, data display and data verification. This study found that social capital that strengthens the resilience and immunity of Salafi education from external threats includes several things; financial capital, social bonding, social linking, curriculum branding, and the boarding school system. The acceptance and appreciation of the community along with the increasingly widespread field of da'wah for Salafi groups in Lombok are strong indications that shows Salafist educational institutions have better prospects, even in the future. On the other hand, the rapid development of Salafi education in Lombok has become a place for the proliferation of Salafi proponents and purificative spirits. Thus, this fact will certainly have the potential to increase tensions in the future, especially ideological conflicts, in the midst of the majority moslems Lombok community whom adhere to Ahlussunah wal-jama'ah.